Targeted remodeling of the human gut microbiome using Juemingzi (Senna seed extracts) - Narrowe, Adrienne B.; Lemons, Johanna M. S.; Mahalak, Karley K.; Firrman, Jenni; Abbeele, Pieter Van den; Baudot, Aurélien; Deyaert, Stef; Li, Yanfang; Yu, Liangli (Lucy); Liu, LinShu (Frontiers in Cellular and Infection Microbiology, 2024)
The genus Senna contains globally distributed plant species of which the leaves, roots, and seeds have multiple traditional medicinal and nutritional uses. Notable chemical compounds derived from Senna spp. include sennosides and emodin which have been tested for antimicrobial effects in addition to their known laxative functions. However, studies of the effects of the combined chemical components on intact human gut microbiome communities are lacking. This study evaluated the effects of Juemingzi (Senna sp.) extract on the human gut microbiome using SIFR® (Systemic Intestinal Fermentation Research) technology. After a 48-hour human fecal incubation, we measured total bacterial cell density and fermentation products including pH, gas production and concentrations of short chain fatty acids (SCFAs). The initial and post-incubation microbial community structure and functional potential were characterized using shotgun metagenomic sequencing. Juemingzi (Senna seed) extracts displayed strong, taxon-specific anti-microbial effects as indicated by significant reductions in cell density (40%) and intra-sample community diversity. Members of the Bacteroidota were nearly eliminated over the 48-hour incubation. While generally part of a healthy gut microbiome, specific species of Bacteroides can be pathogenic. The active persistence of the members of the Enterobacteriaceae and selected Actinomycetota despite the reduction in overall cell numbers was demonstrated by increased fermentative outputs including high concentrations of gas and acetate with correspondingly reduced pH. These large-scale shifts in microbial community structure indicate the need for further evaluation of dosages and potential administration with prebiotic or synbiotic supplements. Overall, the very specific effects of these extracts may offer the potential for targeted antimicrobial uses or as a tool in the targeted remodeling of the gut microbiome.